2016
DOI: 10.9775/kvfd.2016.15665
|View full text |Cite
|
Sign up to set email alerts
|

Kedilerde MI ve MII Oositleri Kullanilarak Somatik Klonlama

Abstract: Animal production via SCNT provides a unique tool for protection of valuable individuals, conservation of vulnerable and endangered species and production of transgenic animals. A total of 167 MI and 219 MII stage oocytes were used as the material of the study. The oocytes were enucleated at 44 h after in vitro maturation by aspiration of the polar body and the MI or MII plates. Cycling granulosa cells were used for nuclear transfer. Cell fusion was induced with DC pulses of 2.0 kV/cm 60µs, 0.1s apart (2x) del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…It is revealed that in vitro fertilized cat oocytes were more successful than the control group, in terms of cleavage and further embryo development in vitro (Yoshhida et al, 2022). The temperature of the transport solution was preferred by some researchers as warm (22-38 o C) (Karja et al, 2002;Merlo et al, 2005;Güriş and Birler, 2011;Evecen et al, 2016), and by some researchers as cold (5 o C) (Johnston et al, 1989;Wolfe and Wildt, 1996;Evecen et al, 2002). The ability of oocytes obtained after storing cat ovaries in cold environments for a long time to mature and be fertilized in vitro provides significant contributions to the protection of wildlife and endangered species (Wolfe and Wildt, 1996;Evecen et al, 2010;Arıcı et al, 2022).…”
Section: In Vitro Technologies a Collection And Transport Of Ovariesmentioning
confidence: 99%
See 3 more Smart Citations
“…It is revealed that in vitro fertilized cat oocytes were more successful than the control group, in terms of cleavage and further embryo development in vitro (Yoshhida et al, 2022). The temperature of the transport solution was preferred by some researchers as warm (22-38 o C) (Karja et al, 2002;Merlo et al, 2005;Güriş and Birler, 2011;Evecen et al, 2016), and by some researchers as cold (5 o C) (Johnston et al, 1989;Wolfe and Wildt, 1996;Evecen et al, 2002). The ability of oocytes obtained after storing cat ovaries in cold environments for a long time to mature and be fertilized in vitro provides significant contributions to the protection of wildlife and endangered species (Wolfe and Wildt, 1996;Evecen et al, 2010;Arıcı et al, 2022).…”
Section: In Vitro Technologies a Collection And Transport Of Ovariesmentioning
confidence: 99%
“…In Vitro Maturation Media: Because there is no medium specifically designed for the in vitro maturation of cat oocytes, researchers use media that is used for other mammalian oocytes. The most commonly used media are; TCM 199 (Karja et al, 2002;Evecen et al, 2016;Evecen et al, 2002;Evecen et al, 2003a), Ham's F-10 (Evecen et al, 2016Evecen et al, 2003a). Synthetic Oviduct Fluid (Evecen et al, 2010;Evecen et al, 2009;Evecen et al, 2004), and Eagle's Minimal Essential Medium (Wolfe and Wildt, 1996).…”
Section: In Vitro Maturationmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro maturation was performed as described in our previous study [15] . In brief, the IVM medium was modified Synthetic Oviduct Fluid, supplemented with 10 µg/mL follicle stimulating hormone (FSH), 10 µg/mL luteinizing hormone (LH), 4% bovine serum albumin (BSA, Fraction V) and antibiotics.…”
Section: In Vitro Maturation (Ivm)mentioning
confidence: 99%